Public spaces and night life - Góis, Marcos Paulo Ferreira de (Geografares, 2018)
The purpose of this article is to discuss some aspects of the relationship between nightlife and public spaces of a big city. The attempt is to demonstrate the significance of space for the existence of democratic social practices between a public during the night. From the observation of the case of Rio de Janeiro, practices, conflicts and negotiations patterns were noted and helped to think about the emergence of public spaces as a scenery for nightlife.Keywords: night; social practices; publicity.